PENINGKATAN HASIL BELAJAR AKIDAH AKHLAQ MATERI BERPERILAKU TERPUJI MELALUI METODE EXAMPLE NON-EXAMPLE SISWA KELAS IV MADRASAH IBTIDAIYAH TANJUNGANOM - Nurul Lailiyah (CV Edujavare Publishing, 2024)
This research is focused on efforts to improve student learning outcomes. In this study using the Class Action Research (PTK) method which has a distinctive feature, namely the existence of a cycle system. Cycles are the stages in carrying out research actions. Classroom action research aims to develop the most efficient and effective learning strategies in natural situations (not experimentation). The result of this study is that the Examples Non Examples method can improve the learning outcomes of Akidah Akhlaq Material Behaving Commendably in grade IV students of Madrasah Ibtidaiyah Tanjunganom